IMPLEMENTASI PENDIDIKAN KARAKTER SEBAGAI UPAYA MEWUJUDKAN PERILAKU PEDULI SOSIAL SISWA SMP NEGERI 1 SALEM - Berliana Putri, Sabila; Suneki, Sri (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
This study aims to describe the implementation of character education in fostering students' social care behavior at SMP Negeri 1 Salem. The focus is on how social values such as empathy, responsibility, and mutual cooperation are instilled through a holistic educational approach that goes beyond cognitive aspects.The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. Informants included Civics Education (PPKn) teachers, Guidance and Counseling (BK) teachers, and students.The findings reveal that character education is implemented through three main approaches: habituation, role modeling, and involvement in social activities. Character values are integrated into Civics Education lessons, extracurricular activities, and counseling services such as the "Teman Curhat" (Peer Listener) program. Students demonstrate social care behavior through actions such as helping peers, maintaining school cleanliness, and actively participating in communal work.Supporting factors include active teacher roles, supportive school programs, and parental involvement. Meanwhile, the challenges include students' lack of awareness and negative external influences.In conclusion, well-planned and comprehensive character education effectively shapes students’ social care behavior. The involvement of all school elements plays a crucial role in creating a conducive environment for reinforcing social values among students.